SINERGI PERANCANGAN ZONA KONSERVASI DAN REKREASI PADA KAWASAN MANGROVE PULAU GALANG - Yusuf Ariyanto (Universitas Tribhuwana Tunggadewi, 2020)
Galang Island region's potential development into a tourism area depends on the physical potential, diversity of flora and fauna and activities that support the economic sector for residents around Galang Island. There are two types of ecotourism development recommendations, one concerning conservation which aims to preserve ecosystems and the second is the use of natural beauty as tourism background and facilities that support the surrounding resident's economy. The problem is how the two tourism recommendations can work together and what kind of synergy the recommendations are like. Through identification stages of the flora and fauna types and analysis of the economic activities of residents around Galang Island, produce a mapping of the potential that can be developed into a tourism area. In the ideation stage, the potential analysis can be realized by functional zone, namely conservation zones, recreation zones and their relationship to regional boundaries and the synergy relationship formed through the circulation concept. By the zones and circulation concept, the visualization phase will be more detailed explaining by the atmosphere that was formed as a synergy form in the Galang Island region design